Comparison of the cerebral activities exhibited by expert and novice visual communication designers during idea incubation. Issue 4 (2nd October 2019) - Liang, Chaoyun; Chang, Chi-Cheng; Liu, Yu-Cheng
ABSTRACT: Scientific data regarding the conception of design-related ideas are increasing, but the mechanisms underlying conceptual imagination remain unclear. The current study aimed to identify the sites of cerebral activity related to pictorial stimulation and to compare the results of electroencephalography for expert and novice designers engaging in tasks involving conceptual imagination. The experiments revealed that (i) the brain activities of virtual experience designers were notably stimulated in the prefrontal and temporal cortices; (ii) the spectral power levels of experts were higher than those of novices, except with regard to sensibility stimulation in the left temporal cortex; and (iii) the differences between experts and novices in the results for the theta and alpha bands in the prefrontal cortex were statistically significant.